(untitled) (INTERNATIONAL JOURNAL OF MACHINE LEARNING AND CYBERNETICS (IJMLC), 2024)
Artificial Intelligence (AI) and Machine Learning (ML) have transformed numerous industries, including healthcare. Predictive analytics, a subset of data analytics that employs ML algorithms to examine current and historical data for forecasting future events, has become vital in healthcare for enhancing patient outcomes, lowering costs, and optimizing resource management. This paper examines the influence of machine learning on predictive analytics in healthcare, highlighting its applications, advantages, challenges, and future prospects.